Design, development and optimization of tedizolid phosphate carbopol based emulgel for skin drug delivery - Madhavi Nimmathota; Sravani Chokkarapu; Akshitha Tirumali; Umamaheshwara Rao Vattikuti (Journal of Applied Pharmaceutical Research, 2026)
Background: Tedizolid phosphate (TZP) is effective against Gram-positive pathogens. It is used most widely in skin infections. Currently, there is no development of emulgels with this novel antibiotic molecule. Hence, the current research focused on developing emulgels for effective topical antimicrobial action to overcome disadvantages associated with oral drug delivery. Methodology: The drug spectroscopic method was developed using a UV-visible spectrophotometer. The o/w emulsions were prepared and incorporated into a gel base to form an emulgel. The prepared emulgels were subjected to physicochemical, IR spectral, antimicrobial, and biophysical analysis. Results and Discussion: Physical examination revealed clear emulgel texture for all test formulations, with maximum spreadability and rheology for carbopol 934 compared to HPMCK 15 and sodium CMC bases. The optimized carbopol 934-based EF7 formulation showed 86% in vitro drug release and 73% ex vivo drug release in 12 hours, respectively. The FTIR studies clearly indicate no incompatibility among the drug and excipients. All physicochemical parameters confirmed controlled release, and FTIR studies confirmed no incompatibility. The optimized emulgel showed good bacterial growth inhibition, and pathological studies confirmed the absence of alteration of porcine ear skin structure. Conclusion: The results indicate that the optimized formulation is suitable for the treatment of acute skin infection.